Ionization effects on spectral signatures of quantum-path interference in high-harmonic generation - Holler, M; Zaïr, A; Schapper, F; Auguste, T; Cormier, E; Wyatt, A; Monmayrant, A; Walmsley, I; Gallmann, L; Salières, P; Keller, U; Zair, A; et al. (OSA, 2009)
The interference between the emission originating from the short and long electron quantum paths is intrinsic to the high harmonic generation process. We investigate the universal properties of these quantum-path interferences in various generation media and discuss how ionization effects influence the observed interference structures. Our comparison of quantum-path interferences observed in xenon, argon, and neon demonstrates that our experimental tools are generally applicable and should also allow investigating more complex systems such as molecules or clusters.